The effect of retrogression and re-aging treatment on mechanical and tribological features of AA7075 aluminium alloyEinfluss der Retrogressions- und Reaging-Behandlung auf die mechanischen und tribologischen Eigenschaften der Aluminiumlegierung AA7075 - Ozer, G.; Gecu, R.; Karaaslan, A. (WILEY-V C H VERLAG GMBH, 2019)
In this study, T651-applied AA7075 alloy was subjected to retrogression and re-aging (RRA) process. Various retrogression temperatures (180 degrees C, 280 degrees C, 370 degrees C) and times (15 min, 30 min, 90 min) were used to determine the effects of temperature and time on the mechanical and tribological properties of the AA7075 alloy. All re-aging stages were performed at 120 degrees C for 24 hours. Retrogression and re-aging-applied specimens were characterized by scanning electron microscope, transmission electron microscope, x-ray diffraction, Charpy V-notch impact and tensile tests. Brinell hardness measurements and ball-on-disc type tribometer measurements by using AISI 316 ball as a counterpart have also been conducted. Grain boundary precipitates in the T651-applied specimen was transformed from continuous to the discontinuous structure after retrogression and re-aging process. Continuous MgZn2 precipitates at grain boundaries were disintegrated and re-precipitated along the grain boundaries. The sizes of intragranular precipitates have become coarsened by comparison with the T651 condition. Hardness, tensile strength and wear resistance were decreased whereas impact toughness values were increased with increasing retrogression temperature and time. The best wear resistance was obtained in the sample treated at 180 degrees C for 15 minutes.
Keywords: AA7075; retrogression and re-aging; wear; mechanical properties; tribological features; WEAR BEHAVIOR; ALLOY; Materials Science